Eyelid Reconstruction - Freitag, Suzanne K. (Thieme, 2020)
Highly practical eyelid surgery resource informs important reconstruction decisions and strategies Skin malignancies frequently affect the periocular area, necessitating excision followed by eyelid reconstruction. Periocular trauma is also quite common, and because of the highly complex regional anatomy, requires expertise for effective reconstruction. Preparation by ophthalmic plastic surgeons prior to periorbital reconstruction is often not possible due to the unpredictability of defects left after Mohs micrographic surgeons clear tumor margins or in cases of trauma. Eyelid Reconstruction by.